Bitter taste receptor T2R38 is expressed on skin-infiltrating lymphocytes and regulates lymphocyte migration - Sakakibara, Moe; Sumida, Hayakazu; Yanagida, Keisuke; Miyasato, Sosuke; Nakamura, Motonao; Sato, Shinichi (Scientific reports, 2022)
Bitter taste receptors (T2Rs) are G protein-coupled receptors involved in the perception of bitter taste on the tongue. In humans, T2Rs have been found in several sites outside the oral cavity. Although T2R38 has been reported to be expressed on peripheral lymphocytes, it is poorly understood whether T2R38 plays immunological roles in inflammatory skin diseases such as atopic dermatitis (AD). Then, we first confirmed that T2R38 gene expression was higher in lesional skin of AD subjects than healthy controls. Furthermore, skin T2R38 expression levels were correlated with serum thymus and activation-regulated chemokine and IgE levels in AD patients. In lesional skin of AD, section staining revealed that CD3 + T cells in the dermis were T2R38 positive. In addition, flow cytometry analysis showed T2R38 expression in skin T cells. Migration assays using T2R38-transduced Jurkat T cell leukemia cells revealed that T2R38 agonists exerted a dose-dependent migration inhibitory effect. Moreover, skin tissue extracts, as well as supernatants of cultured HaCaT keratinocytes, caused T2R38-dependent migration inhibition, indicating that there should be an endogenous ligand for T2R38 in the skin epidermis. These findings implicate T2R38 as a migratory inhibitory receptor on the skin-infiltrating lymphocytes and as a therapeutic target for allergic/inflammatory skin diseases.